Brazilian instrument for investigating adverse events in health: validation study. - Mello, Lucas Rodrigo Garcia de; Christovam, Barbara Pompeu; Rebustini, Flávio; Moreira, Ana Paula Amorim; Moraes, Érica Brandão de; Paes, Graciele Oroski (Acta Paulista de Enfermagem, 2024)
Objective: To build the Brazilian instrument for investigating adverse health events and evaluate the evidence of content validity and the response process. Methods: This psychometric study was conducted according to the Standards for Education and Psychological Testing in the following stages: search for evidence of content validity and response process. In the content evidence, 46 experts from all regions of Brazil participated. In the response process, 76 professionals from 31 health institutions participated. The Statistical Package for the Social Sciences program was used for the distribution of quantitative variables and synthesis, via the calculation of descriptive statistics. In the content evidence stage, the acceptable Content Validity Ratio (CVR) greater than the expected critical CVR for N judges was used; the critical CVR of 0.35 was used in this study. The focus group has been performed for the response process. Results: In total, 46 experts participated in the content validation stage, predominantly training nurses (84.8%), and nurses who graduated 11 years ago (60.7%) or more. The results obtained for each level in content validation were as follows: levels I, II, and III respectively presented the following CVR values: 0.88, 0.76, and 0.97. In the response process stage, adjustments to the nomenclature and sequence of steps were performed. Conclusion: Building and validating the first Brazilian Instrument for Investigating Adverse Events in Health was possible with the necessary sources to ensure the content and response process. The best evidence articulated with national and international references was considered, making it possible to improve investigation systems in private and public health institutions.